Aluminum / carbon fiber / diamond composite material capable of generating binding layer in situ under turbulence impact, cooling fin and preparation method of aluminum / carbon fiber / diamond composite material

By using the method of in-situ generation of bonding layers under turbulent impact in aluminum-based composites, a double-scale thermal conductivity network and high binding strength aluminum/carbon fiber/diamond composites are formed, which solves the problems of insufficient thermal conductivity and low production efficiency of existing aluminum-based composites, and achieves high efficiency of heat dissipation and high production efficiency.

CN119753389AActive Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411945162.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The thermal conductivity of existing aluminum-based composite materials is insufficient, which cannot meet the heat dissipation needs of high-end chips. At the same time, the production efficiency of traditional aluminum alloy heat sinks is low.

Method used

The aluminum/carbon fiber/diamond composite material that generates a bonding layer in situ under turbulent impact is used. The AlTiSi alloy is used as the matrix, and the reinforcement is mainly composed of large-scale diamond particles and small-scale carbon fibers as the auxiliary to form a double-scale thermal conductivity network. During the stirring and casting process, the binding products of Ti, Si and C are reacted in situ to improve the interface binding strength.

Benefits of technology

It significantly improves the thermal conductivity of composite materials, reaching about 600-900W/(m·K), meeting the heat dissipation needs of high-end chips, and improving production efficiency. It has low material density and adjustable expansion coefficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753389A_ABST
    Figure CN119753389A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum / carbon fiber / diamond composite material capable of generating a bonding layer in situ under turbulence impact, a cooling fin and a preparation method of the cooling fin, and belongs to the technical field of composite material preparation. Comprising the steps that AlTiSi / carbon fiber mother alloy is prepared through stirring and casting, the mother alloy is melted and permeated into a mold filled with diamond to obtain the composite material cooling fin, high and low temperature heat treatment is conducted under atmosphere protection, and the final aluminum / carbon fiber / diamond composite material cooling fin is obtained. Under the combined action of in-situ reaction and turbulent flow impact, the carbon fibers are thoroughly scattered to form a uniform and fine heat-conducting network. In a heat conduction network formed by a carbon material, large-size diamonds are used as a main body, and carbon fiber networks with a micron scale are uniformly distributed in gaps of a diamond network. After the Ti and the Si are jointly added, the interface reaction of the composite material is sufficient, the interface thermal resistance is small, and the bonding strength is high. By adjusting the sizes and proportions of diamond and carbon fiber particles, a combination with better thermal conductivity and expansion coefficient can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of novel composite materials, and relates to an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, a heat sink and a preparation method thereof. Background Art

[0002] The main purpose of thermal management is to quickly remove the heat generated by semiconductor devices to ensure the normal operation of core components. Thermal management generally adopts a multi-level heat dissipation mode. In addition to requiring a low thermal expansion coefficient that matches the chip in the direction parallel to the chip plane, the first-level heat dissipation system also needs to have a high thermal conductivity in the direction perpendicular to the chip plane. Subsequently, a secondary heat dissipation system is used to conduct the heat in the primary heat dissipation material to the air. Since the secondary heat dissipation needs to exchange heat with the air, it often requires a relatively large contact area. At this time, the density and heat dissipation capacity of the heat sink will be equally important.

[0003] With the continuous development of 5G technology, the volume of integrated circuit chips and electronic components in base station equipment continues to shrink, while the power density increases rapidly. This leads to an increase in the heat generated by the equipment, and heat diffusion becomes a problem that needs to be solved urgently. Aluminum has a series of advantages such as low price, low density, and corrosion resistance, and is the preferred material for the secondary heat dissipation system. Carbon materials represented by diamond, carbon fiber, carbon nanotubes, graphene, etc. have thermal conductivity far exceeding conventional materials, and the linear expansion coefficient is low and the density is small. At present, the thermal conductivity of aluminum-based composite materials is generally low (such as CN113802080A, CN103949613A), and gradually cannot meet the urgent demand for high thermal conductivity of the secondary heat dissipation system. In addition, traditional aluminum alloy heat sinks are mainly assembled by rolling combined with welding, and the process is multi-process and the production efficiency is low. If the die-casting method is used to achieve one-piece molding, the production efficiency will be greatly improved. How to take into account the thermal conductivity, density and production efficiency of the heat sink is the main problem facing the current secondary heat dissipation system.

[0004] Patent CN113444988A discloses a method for preparing a high thermal conductivity dual carbon material reinforced aluminum-based composite material, which is first coated with a TiC coating on the surface of carbon fiber to prepare a TiC-carbon fiber powder, and then coated with a TiC coating on the surface of diamond to prepare a TiC-diamond powder, and then the TiC-diamond powder is mixed with aluminum liquid to prepare an intermediate composite material, and finally the TiC-carbon fiber powder and the intermediate composite material are compounded by a gas pressure infiltration method to obtain a high thermal conductivity dual carbon material reinforced aluminum-based composite material. In order to improve the interface bonding between aluminum and carbon, the carbon fiber and the diamond surface are coated with a TiC coating in advance. However, when the carbon fiber in the patent is coated with a TiC coating, since the carbon fiber is micrometer-scale and has a large surface area, agglomeration is inevitable. When the TiC coating is coated on the surface of the carbon fiber, the inside of the agglomerate cannot be coated with TiC, and the surface modification effect is lost, resulting in the carbon fiber being unable to be truly evenly dispersed. In addition, the patent provides a TiC coating in advance, but the bonding strength between the TiC coating and the aluminum substrate still needs to be improved. The aluminum substrate and the TiC coating cannot form a chemical bond level bond, but tend to be physically bonded. Moreover, the morphology and size of the TiC coating provided in advance are not suitable for perfect bonding with the aluminum substrate. Therefore, in order to further improve the dispersion effect of carbon fiber and the bonding strength of the aluminum-carbon interface, thereby facilitating phonon conduction, the present invention is designed. Summary of the invention

[0005] In view of the problems of insufficient thermal conductivity of existing aluminum-based materials and low production efficiency of heat sinks, the present invention provides an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, a heat sink and a preparation method thereof. The composite material can greatly improve thermal conductivity, thereby meeting the growing heat dissipation needs of high-end chips.

[0006] The invention provides an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact. The composite material takes an AlTiSi alloy as a matrix, and a reinforcement body mainly composed of large-scale diamond particles and supplemented by small-scale carbon fibers. The large-scale diamond particles are connected to form a diamond skeleton, and the small-scale carbon fibers are evenly and densely dispersed in the gaps of the diamond skeleton. The large-scale diamond particles and the small-scale carbon fibers are connected to form a dual-scale heat conduction network. Under turbulent impact, a bonding layer is in-situ formed at the junction of an aluminum matrix and carbon fibers, and the bonding layer is a bonding product of Ti, Si and C. A bonding layer is also in-situ formed at the junction of the aluminum matrix and the diamond particles.

[0007] The present invention also provides a method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, comprising the following steps:

[0008] 1) Melt pure Al, AlTi master alloy and AlSi master alloy at high temperature, and control the melt temperature at 1200-1500°C;

[0009] 2) The AlTiSi / carbon fiber master composite material is prepared by a non-contact stirring casting process: after the alloying is completed, small-scale carbon fibers are added to the melt while stirring and cooling to 700-900°C, stirring is stopped, and then the melt is rapidly cooled to obtain the AlTiSi / carbon fiber master composite material; in this process, an in-situ reaction occurs at the interface between the carbon fiber and the aluminum matrix, and then a bonding layer is formed on the surface of the carbon fiber. Due to the small size of the carbon fiber, the surface area is large, and agglomerates are inevitably formed. However, under the turbulent impact formed by high-speed stirring, the agglomerates will be impacted by vortices of different sizes and thus broken, thereby reacting in situ at the new surface of the agglomerates, and then breaking and reacting again until the agglomerates are broken, achieving uniform dispersion and uniform reaction;

[0010] 3) Select large-scale diamond particles, add a small amount of alcohol, mix them and put them into a graphite mold, which will accumulate to form a diamond skeleton;

[0011] 4) placing the graphite mold into an integral mold with an upper opening, and placing the AlTiSi / carbon fiber mother composite material into the upper end of the integral mold;

[0012] 5) First evacuate the mold, then heat it to 900-1500°C, the molten AlTiSi / carbon fiber master composite material will gradually fill the overall mold, then introduce gas and maintain a positive pressure of 5-15MPa, or apply mechanical pressure to infiltrate the molten blank into the gaps of the diamond skeleton, and cool it with the furnace to obtain the aluminum / carbon fiber / diamond composite material.

[0013] The present invention also provides a method for preparing a heat sink, which utilizes a method for preparing an aluminum / carbon fiber / diamond composite material that generates a bonding layer in situ under turbulent impact, and adopts an atmosphere-protected rapid temperature rise and fall furnace for heat treatment. The aluminum / carbon fiber / diamond composite material after demolding is heat treated at 500 to 600 degrees Celsius for 4 to 6 hours under atmosphere protection, and then rapidly cooled and then heat treated at 250 to 350 degrees Celsius for 1 to 5 hours, and then cooled in the furnace to obtain the heat sink.

[0014] Furthermore, the large-scale diamond particles have a particle size range of 50 to 800 microns and a volume fraction of 50% to 80%; the small-scale carbon fibers have a diameter of 2 to 20 microns, a length of 20 to 200 microns, and a volume fraction of 1% to 20%.

[0015] Furthermore, the Ti element content ranges from 0.2 to 3 wt.%, and the Si element content ranges from 0.2 to 2 wt.%.

[0016] Furthermore, the large-scale diamond particles have a particle size range of 100 to 150 microns, and the small-scale carbon fibers have a diameter of 5 to 10 microns and a length of 50 to 100 microns.

[0017] Furthermore, the Ti element content ranges from 0.4 to 1 wt.%, and the Si element content ranges from 0.4 to 1 wt.%.

[0018] The method of the present invention is also applicable to the preparation of metal-based composite materials such as copper alloys and magnesium alloys.

[0019] Compared with the prior art, the beneficial technical effects of the present invention are:

[0020] (1) Under the combined action of in-situ reaction and turbulent impact, the carbon fibers are completely broken up to form a uniform and fine heat-conducting network. Due to the small size of carbon fibers, the surface area is large, and agglomerates are inevitably formed. However, under the turbulent impact formed by high-speed stirring, the agglomerates will be impacted by vortices of different sizes and thus broken up, so that in-situ reaction occurs on the new surface of the agglomerates, and the agglomerates are broken up again and reacted again until the agglomerates are broken up, achieving uniform dispersion and uniform reaction.

[0021] (2) The interfacial bonding strength formed by the in-situ reaction is higher than the bonding strength between the pre-provided TiC coating and the aluminum substrate. In the present application, a bonding layer, such as a TiC or SiC layer, is formed by the in-situ reaction during the stirring casting process. The layer is chemically bonded to the aluminum substrate. Compared with the pre-provided TiC coating, the aluminum substrate and the TiC coating cannot form a chemical bond-level bond, but tend to be physically bonded. In addition, the in-situ reaction can control the size and morphology of the generated bonding layer, forming a thin and uniform bonding layer on the surface of the carbon material, while the directly added titanium carbide layer is difficult to control the morphology of the carbide formed on the surface of the carbon material.

[0022] (3) Carbon materials of different scales work together to build a multi-scale, efficient thermal conductive network. In the thermal conductive network formed by carbon materials, large-sized diamonds are the main body, and the gaps in the diamond network are evenly distributed micrometer-scale carbon fiber networks. Experimental results show that the new composite material has a high thermal conductivity, which can reach about 600 to 900 W / (m·K). In addition, by adjusting the particle size and proportion of diamonds and the proportion of carbon fibers, the expansion coefficient of the resulting composite material can be effectively adjusted to make it closer to the expansion coefficient of the primary heat dissipation system. The composite material has low density, high thermal conductivity, and an adjustable expansion coefficient.

[0023] (4) The interface reaction is sufficient, the interface thermal resistance is small, the bonding strength is high, and the thermal conductivity loss after high and low temperature impact is small. The joint addition of Ti and Si is used to achieve the connection at the aluminum-carbon interface. The Ti and Si elements will react with the surface carbon atoms of diamond and carbon fiber during the stirring, infiltration process and high-temperature heat treatment process to form a carbide layer of a certain thickness on the surface of the carbon material. This transition layer can greatly improve the bonding strength of the aluminum-carbon interface on the one hand, and is also beneficial to the conduction of phonons on the other hand. The joint addition of Ti and Si is conducive to the control of the thickness and uniformity of this interface layer, thereby achieving a series of advantages such as low interface thermal resistance, high interface bonding strength, and resistance to high and low temperature impact. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the morphology of the original powder of the carbon fiber described in the present invention.

[0025] Figure 2 This is the morphology of the original diamond powder described in the present invention.

[0026] Figure 3 This is a fracture picture of the final aluminum / carbon fiber / diamond composite material described in the present invention.

[0027] Figure 4 This is the element spectrum result of the final aluminum / carbon fiber / diamond composite material described in the present invention. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] The embodiment of the present invention is an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, a heat sink and a preparation method thereof, comprising the following steps:

[0031] Firstly, AlTiSi / carbon fiber master alloy was prepared by non-contact stirring casting process;

[0032] 1) Pure Al, AlTi master alloy and AlSi master alloy are melted at a high temperature of 1200 degrees Celsius, and cast to obtain Al-1Ti-0.5Si master alloy;

[0033] 2) Stirring speed is 1500 rpm, and wait for 5 vol.% carbon fiber (such as Figure 1As shown, the average diameter of the carbon fiber is 10 microns and the length is 200 microns). After sufficient stirring, the melt is quickly cooled to 700 degrees Celsius, stirring is stopped, and the ingot is allowed to cool rapidly to obtain an AlTiSi master alloy.

[0034] Secondly, a vacuum pressure furnace is used to melt the AlTiSi / carbon fiber master alloy and infiltrate it into the diamond skeleton. The specific steps are as follows:

[0035] 1) Diamond particles with an average particle size of 500 microns and a content of 50 vol.% (such as Figure 2 As shown in the figure, put it into the graphite mold of required thickness, and the diamonds will accumulate to form a loose skeleton;

[0036] 2) placing the above mold into an integral mold with an upper opening, and placing the AlTiSi / carbon fiber master alloy into the upper end of the integral mold with an upper opening;

[0037] 3) First, evacuate the chamber and then heat it to 1200 degrees Celsius. The molten preform will gradually fill the upper opening of the mold. Then, gas is introduced and the positive pressure is maintained at 15 MPa. The molten preform will penetrate into the gaps of the diamond skeleton and cool with the furnace.

[0038] Finally, the composite material after demoulding was heated to 500 degrees Celsius for 5 hours, and then quickly cooled; then heated to 300 degrees Celsius for 2 hours, and cooled with the furnace to obtain the desired composite material (such as Figure 3 The final composite material fracture picture is shown. Figure 4 (Figure 2 is the result of element spectrum of carbide on the surface of diamond on the fracture).

[0039] Its performance data is shown in Table 1.

[0040] Table 1 Performance data of aluminum-carbon composite material in Example 1

[0041]

[0042] Example 2

[0043] The embodiment of the present invention is an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, a heat sink and a preparation method thereof, comprising the following steps:

[0044] Firstly, AlTiSi / carbon fiber master alloy was prepared by stirring casting process;

[0045] 1) Pure Al, AlTi master alloy and AlSi master alloy are melted at a high temperature of 950 degrees Celsius, and cast to obtain Al-1.2Ti-0.6Si master alloy;

[0046] 2) The stirring speed is 2000 rpm. After the carbon fiber (the average diameter of the carbon fiber is 10 microns and the length is 200 microns) with a content of 10 vol.% is fully stirred, the melt is quickly cooled to 700 degrees Celsius, the stirring is stopped, and the ingot is allowed to cool rapidly to obtain the AlTiSi / carbon fiber master alloy.

[0047] Secondly, a vacuum pressure furnace is used to melt the AlTiSi / carbon fiber master alloy and infiltrate it into the diamond skeleton. The specific steps are as follows:

[0048] 1) Place diamond particles with an average particle size of 120 microns and a content of 70 vol.% into a graphite mold of the required thickness, and the diamonds will accumulate to form a loose skeleton;

[0049] 2) placing the above mold into an integral mold with an upper opening, and placing the AlTiSi / carbon fiber master alloy into the upper end of the integral mold with an upper opening;

[0050] 3) First, evacuate the chamber, then raise the temperature to 1400 degrees Celsius. The molten pre-blank will gradually fill the upper opening of the mold. Then, gas is introduced and the positive pressure is maintained at 15 MPa. The molten pre-blank is infiltrated into the gaps of the diamond skeleton and cooled with the furnace.

[0051] Finally, an argon-protected rapid heating and cooling furnace was used for high and low temperature heat treatment. The demolded composite material was heated to 500 degrees Celsius for 5 hours and then quickly cooled; then heated to 300 degrees Celsius and kept at this temperature for 2 hours, and cooled with the furnace to obtain the desired composite material.

[0052] Its performance data is shown in Table 2.

[0053] Table 2 Performance data of aluminum-carbon composite material in Example 2

[0054]

[0055]

[0056] Comparative Example 1

[0057] The comparative example of the present invention is an aluminum-carbon composite material and a preparation method thereof, comprising the following steps:

[0058] Firstly, AlTi / carbon fiber master alloy was prepared by stirring casting process;

[0059] 1) Pure Al and AlTi master alloys are melted at a high temperature of 950 degrees Celsius, and cast to obtain Al-1.2Ti master alloy;

[0060] 2) The stirring speed is 2000 rpm. After the carbon fiber (the average diameter of the carbon fiber is 10 microns and the length is 200 microns) with a content of 10 vol.% is fully stirred, the melt is quickly cooled to 700 degrees Celsius, the stirring is stopped, and the ingot is allowed to cool rapidly to obtain the AlTi / carbon fiber master alloy.

[0061] Secondly, a vacuum pressure furnace is used to melt the AlTi / carbon fiber master alloy and infiltrate it into the diamond skeleton. The specific steps are as follows:

[0062] 1) Place diamond particles with an average particle size of 120 microns and a content of 70 vol.% into a graphite mold of the required thickness, and the diamonds will accumulate to form a loose skeleton;

[0063] 2) placing the above mold into an integral mold with an upper opening, and placing the AlTi / carbon fiber master alloy into the upper end of the integral mold with an upper opening;

[0064] 3) First, evacuate the chamber, then heat it to 1500 degrees Celsius. The molten preform will gradually fill the upper opening of the mold. Then, gas is introduced and the positive pressure is maintained at 15MPa. The molten preform will penetrate into the gaps of the diamond skeleton and cool with the furnace.

[0065] Finally, an argon-protected rapid heating and cooling furnace was used for high and low temperature heat treatment. The demolded composite material was heated to 500 degrees Celsius for 5 hours and then quickly cooled; then heated to 300 degrees Celsius and kept at this temperature for 2 hours, and cooled with the furnace to obtain the desired composite material.

[0066] Its performance data is shown in Table 3.

[0067] Table 3 Performance data of aluminum-carbon composite materials in comparative example 1

[0068]

[0069] It can be seen from the comparative data that only adding the alloy element Ti cannot obtain high thermal conductivity, and the thermal conductivity of the material decreases significantly after the hot and cold cycle test. Since the bonding strength between the matrix and carbon is not as good as the effect after the combined addition of Ti and Si, the expansion coefficient is increased.

[0070] The embodiments of the present invention are described in detail, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.

Claims

1. An aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact, characterized in that: The AlTiSi alloy is used as the matrix, and the reinforcement is mainly composed of large-scale diamond particles and supplemented by small-scale carbon fibers. The large-scale diamond particles are connected to form a diamond skeleton, and the small-scale carbon fibers are evenly and densely dispersed in the gaps of the diamond skeleton. The large-scale diamond particles and the small-scale carbon fibers are connected to form a dual-scale heat conduction network. Under turbulent impact, a bonding layer is in-situ formed at the junction of the aluminum matrix and the carbon fibers. The bonding layer is a bonding product of Ti, Si and C, and a bonding layer is also in-situ formed at the junction of the aluminum matrix and the diamond particles.

2. The method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact according to claim 1, characterized in that: The following steps are involved: 1) Melt pure Al, AlTi master alloy and AlSi master alloy at high temperature, and control the melt temperature at 1200-1500°C; 2) The AlTiSi / carbon fiber master composite material is prepared by a non-contact stirring casting process: after the alloying is complete, small-scale carbon fibers are added to the melt while stirring and cooling to 700-900°C, stirring is stopped, and then the melt is rapidly cooled to obtain the AlTiSi / carbon fiber master composite material; In this process, an in-situ reaction occurs at the interface between the carbon fiber and the aluminum matrix, and then a bonding layer is formed on the surface of the carbon fiber. Due to the small size of the carbon fiber, the surface area is large, and agglomerates are inevitably formed. However, under the turbulent impact formed by high-speed stirring, the agglomerates will be impacted by vortices of different sizes and thus broken, so that an in-situ reaction occurs at the new surface of the agglomerate, and then the agglomerates are broken and reacted again until the agglomerates are broken and uniform dispersion and uniform reaction are achieved. 3) Select large-scale diamond particles, add a small amount of alcohol, mix them and put them into a graphite mold, which will accumulate to form a diamond skeleton; 4) placing the graphite mold into an integral mold with an upper opening, and placing the AlTiSi / carbon fiber mother composite material into the upper end of the integral mold; 5) First evacuate the mold, then heat it to 900-1500°C, the molten AlTiSi / carbon fiber master composite material will gradually fill the overall mold, then introduce gas and maintain a positive pressure of 5-15MPa, or apply mechanical pressure to infiltrate the molten blank into the gaps of the diamond skeleton, and cool it with the furnace to obtain the aluminum / carbon fiber / diamond composite material.

3. A method for preparing a heat sink, using the method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact as described in claim 2, characterized in that: The aluminum / carbon fiber / diamond composite material after demoulding is heat treated in an atmosphere-protected rapid temperature rise and fall furnace, and is heat treated at 500-600 degrees Celsius for 4-6 hours under atmosphere protection, and is heat treated at 250-350 degrees Celsius for 1-5 hours after rapid cooling, and is cooled in the furnace to obtain the heat sink.

4. The method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact according to claim 2, characterized in that: The large-scale diamond particles have a particle size range of 50 to 800 microns and a volume fraction of 50% to 80%; the small-scale carbon fibers have a diameter of 2 to 20 microns, a length of 20 to 200 microns, and a volume fraction of 1% to 20%.

5. The method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact according to claim 2, characterized in that: The Ti element content ranges from 0.2 to 3 wt.%, and the Si element content ranges from 0.2 to 2 wt.%.

6. The method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact according to claim 4, characterized in that: The large-scale diamond particles have a particle size range of 100 to 150 microns, and the small-scale carbon fibers have a diameter of 5 to 10 microns and a length of 50 to 100 microns.

7. The method for preparing an aluminum / carbon fiber / diamond composite material with an in-situ generated bonding layer under turbulent impact according to claim 4, characterized in that: The Ti element content ranges from 0.4 to 1 wt.%, and the Si element content ranges from 0.4 to 1 wt.%.

Citation Information

Patent Citations

  • Method for preparing alumino-silicon-carbide high-thermal-conductivity substrate material for high-power module

    CN103949613A

  • Aluminum silicon carbide heat conduction material for high-power charging pile and preparation method of aluminum silicon carbide heat conduction material

    CN113802080A

  • Method for preparing composite material for engine cylinder piston

    CN104087878A

  • Surface-modification three-dimensional-network-carbon-fiber-reinforced composite material and preparing method

    CN105818476A

  • Preparation method of high-thermal-conductivity double-carbon material reinforced aluminum-based composite material

    CN113444988A